ANALISIS KEBIJAKAN PENDANAAN DAN RASIO PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS KOPERASI USAHA DI SURABAYA TAHUN 2008-2012 - WIJAYA, YUNITA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Working capital is one important aspect for the continuity of a business in profit. Working capital financing policy, whether it’s aggressive or conservative, depends on the preference of the managers in companies considering the trade-off between profitability and risk and its influence on profitability. Manager who tends to be careful on working capital financing policy is relatively conservative, whereas the optimistic manager will tend to use aggressive financing policy. Differrent application on working capital funding policy will affect the profits. The purpose of this study was to analyze the working capital funding policy on profitability are moderated by the working capital turnover ratio. This study uses object cooperative businesses in Surabaya during the period 2008-2012. Data are obtained from the Department of Cooperatives and MSMEs the city of Surabaya. Data collection methods used in this study is pooled data documentation technique. The sampling technique used is criteria purposive sampling. The samples used are 91 cooperatives. The analytical techniques used is Multiple Linear Regression Analysis. This analysis is to determine the effect of working capital financing policy and working capital turnover ratio to profitability. The results of this study indicate that the first hypothesis test results is that working capital financing policy has significant negative effect to profitability, so cooperative that uses aggressive working capital financing policies has lower profitability than the cooperative that uses a policy of conservative working capital financing. Second, working capital turnover ratio has no significant effect to profitability. Third, working capital financing policies moderation with working capital turnover ratio have no significant effect to profitability, which means that the results do not have a moderating effect to profitability.